Feasibility of a mean platelet volume standard: an international council for standardization in hematology (ICSH) inter-laboratory study. (17th November 2022) - Harrison, Paul; Price, Joshua; Didembourg, Marie; Johnson, Alan; Baldwin, Samuel; Veronneau, Marcel; Baertlein, Daniel; Shi, Xiaoyong; Machin, Samuel
Abstract: We have evaluated a commercial-fixed porcine platelet preparation (with and without added fixed human red blood cells (RBC)) for the potential standardization of mean platelet volume (MPV) measurements. The standards (Biotechne) were distributed internationally to 19 laboratories including all major hematology instrument manufacturers and academic/pathology laboratories. Overall, the standards demonstrated excellent stability up to 1 month within both MPV values and platelet counts when stored at 4°C. The presence of RBC significantly increased the platelet count and MPV values compared to platelets alone. However, as expected, there were differences in MPV values between different instruments and manufacturers. MPV values were also significantly higher in the whole blood standard compared to the platelet standard in the majority of instruments except with some instruments, where MPV values were significantly higher in the platelet only preparation. To further investigate this phenomenon, two different Platelet MPV preparations (with low and high MPV) in combination with 3 different RBC MCV preparations (with low, normal or high MCVs) were tested to try and further elucidate how RBC populations may impact upon platelet analysis (count, MPV, and PDW) using a single impedance analyzer. Both MPV and MCV values showed good stability over the course of the study for up to 50 days. As expected, the RBC preparation with the lowest MCV had the greatest impact on the MPV. However, this was not observed with an increase in MCV of the RBC or by a larger MPV of the platelet population. To further understand how different gating strategies may also influence results, we investigated the effect of either fixed or floating gate strategies upon MPV raw data from patient samples in a single impedance analyzer. Overall, it was clear that floating and fixed gate strategies also significantly impact upon MPV values. In conclusion, we have demonstrated the potential of an MPV standard with good stability characteristics for calibrating and comparing full blood counters that use different analysis principles, gating and MPV calculations. This may facilitate future instrument calibration and harmonization of results between different technologies.